Preparation process of polymer battery
By using modified polyacrylonitrile and tantalum doped lithium lanthanum zirconium oxygen and other materials in polymer batteries, the safety problems of traditional lithium-ion batteries and the insufficient performance of solid polymer batteries are solved, and high electrical performance, excellent mechanical properties and good flame retardant properties are achieved.
Patent Information
- Application Number
- CN202411607946.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Traditional lithium-ion batteries have safety problems such as liquid leakage, ignition, and explosion. The ratio performance of solid-state polymer batteries is low, has large internal resistance and poor circulation performance. The polymer electrolyte is flammable at high temperatures, which affects safety.
Using a preparation process of a polymer battery, the ionic conductivity and mechanical properties of the electrolyte are improved by combining modified polyacrylonitrile as an electrolyte material, combined with tantalum doped lithium lanthanum zirconium oxygen and bis(trifluoromethanesulfonyl)imide lithium, and the ionic conductivity and mechanical properties of the electrolyte are improved through specific preparation steps and process conditions.
It improves the electrical properties of polymer batteries, enhances the ionic conductivity, mechanical properties and flame retardant properties of the electrolyte, improves the safety and circulation performance of the battery, and has important application value.
Smart Images

Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer batteries, and in particular, relates to a preparation process of a polymer battery. Background Art
[0002] Lithium-ion batteries have the advantages of high operating voltage, high energy density, small size, no memory effect and long life. They are a new type of high-energy battery with higher energy density developed after lead-acid batteries, nickel-cadmium batteries and nickel-metal hydride batteries. They have made rapid progress in the past three decades. Traditional lithium-ion batteries use organic liquid electrolytes such as organic solvents such as ethylene carbonate and propylene carbonate. This type of liquid electrolyte will cause lithium-ion batteries to have safety problems such as leakage, fire and explosion. The safety issues of traditional lithium batteries have attracted great attention.
[0003] Polymer batteries, usually referring to lithium polymer batteries (Lithium Polymer Battery, referred to as Li-poly or Polymer Battery), are a type of secondary battery. Compared with traditional lithium-ion batteries, they have higher energy density, design flexibility, lighter weight and better safety performance. The working principle of lithium polymer batteries is similar to that of liquid lithium-ion batteries, and the main difference lies in the difference in electrolytes. Lithium polymer batteries use solid or colloidal polymer materials as electrolytes instead of liquid electrolytes. This electrolyte is not only safe, but also can conduct lithium ions and act as a diaphragm inside the battery to isolate positive and negative electrode materials and prevent short circuits. However, there is no liquid in solid-state batteries, and the gaps inside and at the interface of electrodes and diaphragms are not filled with liquid. Therefore, the rate performance of solid-state polymer batteries is generally low, the internal resistance is large, and the cycle performance is poor. Not only that, the polymer electrolyte in polymer batteries belongs to polymer materials, and its high-temperature flammable characteristics still bring serious safety hazards to polymer batteries. There is not much advantage in competing with ordinary lithium-ion batteries in the traditional market. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of polymer battery technology. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a preparation process of a polymer battery.
[0005] The purpose of the present invention can be achieved through the following technical solutions: A process for preparing a polymer battery comprises the following steps: The polymer electrolyte is adhered between the positive electrode sheet and the negative electrode sheet to form a core, and then the core is placed in the battery casing. After sealing, formation, sealing and packaging, a polymer battery is obtained.
[0006] Furthermore, the negative electrode plate material is a lithium alloy.
[0007] Furthermore, the positive electrode plate is prepared by the following steps: Place lithium iron phosphate (LEP), polyvinylidene fluoride (binder) and acetylene black (conductive agent) in a mortar and mix well, grind for 0.5-1h, add N-methylpyrrolidone dropwise, and continue grinding until the viscosity is uniform to obtain active slurry. Apply the active slurry evenly on the rough surface of aluminum foil, place it in a vacuum drying oven at 90°C, dry it for 12h, and take it out after it cools to room temperature to obtain the positive electrode sheet.
[0008] Furthermore, the mass ratio of lithium iron phosphate, polyvinylidene fluoride, and acetylene black is 6:2:1.
[0009] Furthermore, the polymer electrolyte is prepared by the following steps: A1. Place modified polyacrylonitrile, tantalum-doped lithium lanthanum zirconium oxide (LLZTO) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in an oven at 100°C and dry for 6 hours to remove excess moisture. Then, add tantalum-doped lithium lanthanum zirconium oxide to N-methyl-2-pyrrolidone (NMP), use a crusher for ultrasonic dispersion to disperse partially agglomerated tantalum-doped lithium lanthanum zirconium oxide, then add lithium bis(trifluoromethanesulfonyl)imide and stir for 1 hour, then add acetic acid to adjust the pH to 7, then add N,N-dimethylformamide (DMF) and modified polyacrylonitrile and stir for 12 hours to obtain a composite electrolyte solution. A2. The composite electrolyte solution was uniformly coated on both sides of a 30 μm thick cellulose membrane by a doctor blade method, and finally dried in a forced air drying at 100° C. for 12 h to obtain a polymer electrolyte.
[0010] Furthermore, the raw materials are calculated in parts by weight as follows: 40-60 parts of modified polyacrylonitrile, 10-20 parts of tantalum-doped lithium lanthanum zirconium oxide, and 4-6 parts of lithium bis(trifluoromethanesulfonyl)imide.
[0011] The prepared polymer electrolyte is prepared by adding inorganic active filler tantalum-doped lithium lanthanum zirconium oxide. The filler can directly participate in ion transport, provide a lithium source, and greatly enhance the ionic conductivity of the polymer electrolyte. The organic / inorganic composite system is adopted to combine the advantages of both, thereby improving the interface performance, the comprehensive performance of the electrolyte and the rate cycle performance of the polymer battery.
[0012] Further, the modified polyacrylonitrile is prepared by the following steps: S1. At room temperature, diphenyl chlorophosphate, 3-butene-1-amine, diethylamine and toluene were stirred and mixed evenly in a three-necked flask equipped with a stirring device under nitrogen protection, the reaction temperature was controlled to 60°C, and the reaction was kept warm for 5 hours. After the reaction was completed, the reaction was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 1; the ratio of diphenyl chlorophosphate, 3-butene-1-amine, diethylamine and toluene was 26.8g:7.1g:15mL:100mL; Diphenyl chlorophosphate and 3-butene-1-amine undergo nucleophilic substitution, and diethylamine removes the hydrogen chloride generated by the reaction to obtain intermediate 1. The specific reaction process is as follows: ; S2. In a three-necked flask equipped with a stirring device, the intermediate 1, AIBN (azobisisobutyronitrile) and toluene were stirred and mixed evenly, and 3-mercaptopropanol was slowly added dropwise. After the addition was completed, the reaction temperature was controlled to 70°C and the reaction was carried out for 4 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of intermediate 1, AIBN, toluene, and 3-mercaptopropanol was 30.3g:0.5g:150mL:9.2g; Under the action of AIBN, the unsaturated carbon-carbon double bond on the intermediate 1 molecule undergoes a thiol-ene click reaction with the thiol group of 3-mercaptopropanol to obtain intermediate 2; ; S3, place polyacrylonitrile powder, zinc acetate dihydrate, ethanolamine and N,N-dimethylformamide in a three-necked flask with a stirrer and a thermometer, gradually heat to 90°C, keep warm for 2 hours and then stop heating, then add N,N-dimethylformamide to dilute, then slowly add dichloromethane while stirring rapidly, filter after stirring for 10 minutes, and repeat this washing 3 times to obtain pre-modified polyacrylonitrile; the ratio of polyacrylonitrile powder, zinc acetate dihydrate, ethanolamine and N,N-dimethylformamide is 20g:2g:25g:200mL; Under the catalysis of zinc acetate dihydrate, the cyano group on the polyacrylonitrile molecule undergoes cyclization to form an oxazoline active group, which provides a reaction site for subsequent reactions to obtain pre-modified polyacrylonitrile. S4. In a three-necked flask equipped with a stirring device, pre-modified polyacrylonitrile, N,N-dimethylformamide and intermediate 2 were stirred and mixed uniformly, and the mixture was kept warm at 70°C for 2 hours. After the reaction was completed, heating was stopped, and N,N-dimethylformamide was added. Toluene was slowly added while stirring rapidly, and the mixture was filtered after stirring for 10 minutes. The mixture was washed repeatedly for 3 times, and the obtained powder was placed in an oven at 60°C and dried to obtain modified polyacrylonitrile; the ratio of pre-modified polyacrylonitrile, N,N-dimethylformamide and intermediate 2 was 20 g:200 mL:35 g. The oxazoline active group in the pre-modified polyacrylonitrile molecule reacts with the hydroxyl group in the intermediate 2 molecule to obtain modified polyacrylonitrile; Polyacrylonitrile has high electrochemical stability, high ionic conductivity, good thermal stability, large electrochemical stability window, and good compatibility with lithium electrodes. By modifying polyacrylonitrile, the number of cyano groups in polyacrylonitrile is reduced, making it less likely to react with lithium ions, reducing the generation of compounds such as imides or imides, and thus improving the mechanical properties of the electrolyte. Moreover, the modified polyacrylonitrile molecules contain PN flame retardant components and sulfur elements, wherein the PN flame retardant components have the synergistic flame retardant effects of phosphorus-based and nitrogen-based flame retardants, which can greatly improve the flame retardant properties of the electrolyte. The added sulfur element has a low electronegativity, and the bonding strength between sulfur and lithium ions is weak, which increases the concentration of free mobile lithium ions, and the radius of sulfur ions is larger than that of oxygen ions, thereby providing wider lattice pores for lithium ions to migrate, thereby enhancing the ionic conductivity of the solid electrolyte. In addition, the organic molecular chains are connected to the polyacrylonitrile polymer molecules through chemical bonding, which improves the long-term stability of the modified polyacrylonitrile performance.
[0013] Beneficial effects of the present invention: 1. The electrolyte in the polymer battery prepared by the present invention is an organic-inorganic composite solid electrolyte. On the one hand, the flexibility of the organic polymer is used to improve the interface contact, and on the other hand, the inorganic material can inhibit the growth of lithium dendrites and enhance the ionic conductivity of the electrolyte; 2. By modifying polyacrylonitrile, its mechanical properties and flame retardant properties are better than those of ordinary polyacrylonitrile, and the ionic conductivity of the electrolyte is also enhanced; Therefore, the polymer battery prepared by the present invention has good electrical properties, and the electrolyte ions in the polymer battery have high conductivity, excellent mechanical properties, and good flame retardant properties, and has important application value in the field of polymer battery technology. DETAILED DESCRIPTION
[0014] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0015] Embodiment 1 Preparation of modified polyacrylonitrile: S1. At room temperature, under nitrogen protection, 26.8 g of diphenyl chlorophosphate, 7.1 g of 3-butene-1-amine, 15 mL of diethylamine and 100 mL of toluene were stirred and mixed uniformly in a three-necked flask equipped with a stirring device. The reaction temperature was controlled to 60° C. and the reaction was kept warm for 5 h. After the reaction was completed, the reaction was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 1; S2. In a three-necked flask equipped with a stirring device, 30.3 g of intermediate 1, 0.5 g of AIBN (azobisisobutyronitrile) and 150 mL of toluene were stirred and mixed evenly, and 9.2 g of 3-mercaptopropanol was slowly added dropwise. After the addition was completed, the reaction temperature was controlled to 70°C and the reaction was carried out for 4 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 2; S3, 20g polyacrylonitrile powder, 2g zinc acetate dihydrate, 25g ethanolamine and 100mL N,N-dimethylformamide were placed in a three-necked flask with a stirrer and a thermometer, and the temperature was gradually raised to 90°C. After keeping the temperature for 2h, the heating was stopped, and 100mL N,N-dimethylformamide was added for dilution. Then, 50mL dichloromethane was slowly added while stirring rapidly, and the mixture was filtered after stirring for 10min. The mixture was washed repeatedly for 3 times to obtain pre-modified polyacrylonitrile; S4. In a three-necked flask equipped with a stirring device, stir and mix 20 g of pre-modified polyacrylonitrile, 100 mL of N,N-dimethylformamide and 35 g of intermediate 2, and react at 70°C for 2 h. After the reaction is completed, stop heating, add 200 mL of N,N-dimethylformamide, and slowly add 50 mL of toluene while stirring rapidly. After stirring for 10 min, filter, and repeat washing 3 times. Dry the resulting powder in a 60°C oven to obtain modified polyacrylonitrile.
[0016] Embodiment 2 Preparation of modified polyacrylonitrile: S1. At room temperature, 53.6 g of diphenyl chlorophosphate, 14.2 g of 3-butene-1-amine, 30 mL of diethylamine and 200 mL of toluene were stirred and mixed in a three-necked flask equipped with a stirring device under nitrogen protection. The reaction temperature was controlled to 60° C. and the reaction was kept warm for 5 h. After the reaction was completed, the reaction was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 1; S2. In a three-necked flask equipped with a stirring device, 60.6 g of intermediate 1, 1.0 g of AIBN (azobisisobutyronitrile) and 300 mL of toluene were stirred and mixed evenly, and 18.4 g of 3-mercaptopropanol was slowly added dropwise. After the addition was completed, the reaction temperature was controlled to 70°C and the reaction was carried out for 4 hours. After the reaction was completed, part of the solvent was first removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 2:1), and the eluent was removed by rotary evaporation to obtain intermediate 2; S3, 40g polyacrylonitrile powder, 4g zinc acetate dihydrate, 50g ethanolamine and 200mL N, N-dimethylformamide were placed in a three-necked flask with a stirrer and a thermometer, and the temperature was gradually raised to 90°C. After keeping the temperature for 2h, the heating was stopped, and 200mL N, N-dimethylformamide was added for dilution, and 100mL dichloromethane was slowly added while stirring rapidly. After stirring for 10min, the mixture was filtered, and the mixture was washed repeatedly for 3 times to obtain pre-modified polyacrylonitrile; S4. In a three-necked flask equipped with a stirring device, stir and mix 40 g of pre-modified polyacrylonitrile, 200 mL of N, N-dimethylformamide and 70 g of intermediate 2, and react at 70°C for 2 h. After the reaction is completed, stop heating, add 200 mL of N, N-dimethylformamide, and slowly add 100 mL of toluene while stirring rapidly. After stirring for 10 min, filter, and repeat washing 3 times. Dry the obtained powder in an oven at 60°C to obtain modified polyacrylonitrile.
[0017] Embodiment 3 Preparation of polymer electrolyte: A1. 40 g of the modified polyacrylonitrile obtained in Example 1, 10 g of tantalum-doped lithium lanthanum zirconium oxide and 4 g of lithium bis(trifluoromethanesulfonyl)imide were placed in an oven at 100° C. and dried for 6 h to remove excess moisture. The tantalum-doped lithium lanthanum zirconium oxide was added to N-methyl-2-pyrrolidone and ultrasonically dispersed using a crusher to disperse partially agglomerated tantalum-doped lithium lanthanum zirconium oxide. Lithium bis(trifluoromethanesulfonyl)imide was then added and stirred for 1 h, followed by acetic acid to adjust the pH to 7. 100 mL of N,N-dimethylformamide and modified polyacrylonitrile were then added and stirred for 12 h to obtain a composite electrolyte solution. A2. The composite electrolyte solution was uniformly coated on both sides of a 30 μm thick cellulose membrane by a doctor blade method, and finally dried in a forced air drying at 100° C. for 12 h to obtain a polymer electrolyte.
[0018] Embodiment 4 Preparation of polymer electrolyte: A1. 50 g of the modified polyacrylonitrile obtained in Example 2, 15 g of tantalum-doped lithium lanthanum zirconium oxide and 5 g of lithium bis(trifluoromethanesulfonyl)imide were placed in an oven at 100° C. and dried for 6 h to remove excess moisture. The tantalum-doped lithium lanthanum zirconium oxide was added to N-methyl-2-pyrrolidone and ultrasonically dispersed using a crusher to disperse partially agglomerated tantalum-doped lithium lanthanum zirconium oxide. The lithium bis(trifluoromethanesulfonyl)imide was then added and stirred for 1 h, followed by acetic acid to adjust the pH to 7. 150 mL of N,N-dimethylformamide and modified polyacrylonitrile were then added and stirred for 12 h to obtain a composite electrolyte solution. A2. The composite electrolyte solution was uniformly coated on both sides of a 30 μm thick cellulose membrane by a doctor blade method, and finally dried in a forced air drying at 100° C. for 12 h to obtain a polymer electrolyte.
[0019] Embodiment 5 Preparation of polymer electrolyte: A1. 60 g of modified polyacrylonitrile obtained in Example 2, 20 g of tantalum-doped lithium lanthanum zirconium oxide and 6 g of lithium bis(trifluoromethanesulfonyl)imide were placed in an oven at 100° C. and dried for 6 h to remove excess moisture. The tantalum-doped lithium lanthanum zirconium oxide was added to N-methyl-2-pyrrolidone and ultrasonically dispersed using a crusher to disperse partially agglomerated tantalum-doped lithium lanthanum zirconium oxide. Lithium bis(trifluoromethanesulfonyl)imide was then added and stirred for 1 h, followed by acetic acid to adjust the pH to 7. 100 mL of N,N-dimethylformamide and modified polyacrylonitrile were then added and stirred for 12 h to obtain a composite electrolyte solution. A2. The composite electrolyte solution was uniformly coated on both sides of a 30 μm thick cellulose membrane by a doctor blade method, and finally dried in a forced air drying at 100° C. for 12 h to obtain a polymer electrolyte.
[0020] Embodiment 6 Preparation of positive electrode sheet: Place 6g of lithium iron phosphate, 2g of polyvinylidene fluoride and 1g of acetylene black in a mortar and mix well, grind for 0.5h, add 50mL of N-methylpyrrolidone, and continue grinding until the viscosity is uniform to obtain an active slurry. Apply the active slurry evenly on the rough surface of aluminum foil, place it in a vacuum drying oven at 90°C, dry it for 12h, and take it out after it cools to room temperature to obtain a positive electrode sheet.
[0021] Embodiment 7 Preparation of polymer battery: The polymer electrolyte prepared in Example 3 is adhered between the positive electrode sheet and the negative electrode sheet prepared in Example 6 to form a core, and then the core is placed in a battery casing, and after sealing, forming, sealing, and packaging, a polymer battery is obtained; The negative electrode plate material is lithium alloy.
[0022] Embodiment 8 Preparation of polymer battery: The polymer electrolyte prepared in Example 4 is adhered between the positive electrode sheet and the negative electrode sheet prepared in Example 6 to form a core, and then the core is placed in a battery casing, and the polymer battery is obtained after sealing, forming, sealing, and packaging. The negative electrode plate material is lithium alloy.
[0023] Embodiment 9 Preparation of polymer battery: The polymer electrolyte prepared in Example 5 is adhered between the positive electrode sheet and the negative electrode sheet prepared in Example 6 to form a core, and then the core is placed in a battery casing, and after sealing, forming, sealing, and packaging, a polymer battery is obtained; The negative electrode plate material is lithium alloy.
[0024] Comparative Example 1 Ordinary polyacrylonitrile of the same mass was used to replace the modified polyacrylonitrile in Example 5, and the remaining steps were the same as those in Example 5 to prepare a polymer electrolyte.
[0025] Comparative Example 2 The polymer electrolyte prepared in Comparative Example 1 was used to replace the polymer electrolyte in Example 9, and the remaining steps were the same as those in Example 9 to prepare a polymer battery.
[0026] The following performance tests were conducted on Examples 3, 4, 5 and Comparative Example 1 with different test standards: The tensile properties were measured using the Meters MTSCMT8535 tensile tester, with the test sample cut into a dumbbell shape with a length of 20 mm, a width of 5 mm, a thickness of approximately 40 μm, and a frequency of 20 Hz; Electrochemical impedance spectroscopy was used to measure the ionic conductivity of solid electrolytes; The national standard GB / T 2406-2008 "Test method for combustion performance of plastics" is used to measure the limiting oxygen index of the sample before and after standing at room temperature for 180 days; The measured results are shown in Table 1: Table 1
[0027] The electrical performance tests were conducted on Example 7, Example 8, Example 9 and Comparative Example 2, and the results are shown in Table 2: Table 2
[0028] It can be seen from the above two tables that the polymer battery prepared in the embodiment of the present invention has good electrical properties, and the electrolyte ions in the polymer battery have high conductivity, excellent mechanical properties, and good flame retardant properties, and has important application value in the field of polymer battery technology.
[0029] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0030] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A process for preparing a polymer battery, characterized in that: The following steps are involved: The polymer electrolyte is adhered between the positive electrode plate and the negative electrode plate to form a pole core, and then the pole core is placed in the battery shell. After sealing, formation, sealing and packaging, a polymer battery is obtained.
2. The process for preparing a polymer battery according to claim 1, characterized in that: The polymer electrolyte is prepared by the following steps: A1, drying modified polyacrylonitrile, tantalum-doped lithium lanthanum zirconium oxide and lithium bis(trifluoromethanesulfonyl)imide, then adding tantalum-doped lithium lanthanum zirconium oxide to N-methyl-2-pyrrolidone, using a crusher for ultrasonic dispersion, then adding lithium bis(trifluoromethanesulfonyl)imide and stirring, adjusting the pH to 7, then adding N,N-dimethylformamide and modified polyacrylonitrile and stirring to obtain a composite electrolyte solution; A2. The composite electrolyte solution was evenly coated on both sides of a 30 μm thick cellulose membrane by a doctor blade method and dried to obtain a polymer electrolyte.
3. The process for preparing a polymer battery according to claim 2, characterized in that: The modified polyacrylonitrile is prepared by the following steps: S1. At room temperature, diphenyl chlorophosphate, 3-butene-1-amine, diethylamine and toluene were stirred and mixed under nitrogen protection, and reacted at 60°C for 5 hours. After the reaction was completed, the mixture was filtered and distilled under reduced pressure to obtain intermediate 1; S2, mixing the intermediate 1, AIBN and toluene evenly, adding 3-mercaptopropanol dropwise, reacting at 70°C for 4h, and after the reaction is completed, rotary evaporation, column chromatography purification, and rotary evaporation to obtain the intermediate 2; S3, placing polyacrylonitrile powder, zinc acetate dihydrate, ethanolamine and N,N-dimethylformamide in a three-necked flask, gradually heating to 90°C, keeping warm for 2 hours and then stopping heating, adding N,N-dimethylformamide for dilution, and then slowly adding dichloromethane while stirring rapidly, stirring for 10 minutes and filtering, and repeatedly washing 3 times to obtain pre-modified polyacrylonitrile; S4. Stir and mix the pre-modified polyacrylonitrile, N,N-dimethylformamide and intermediate 2 evenly, and react at 70°C for 2 hours. After the reaction is completed, stop heating, add N,N-dimethylformamide, and slowly add toluene while stirring rapidly. After stirring for 10 minutes, filter, repeat washing 3 times, and dry to obtain modified polyacrylonitrile.
4. The process for preparing a polymer battery according to claim 3, characterized in that: In step S1, the ratio of diphenyl chlorophosphate, 3-butene-1-amine, diethylamine and toluene is 26.8 g:7.1 g:15 mL:100 mL.
5. The process for preparing a polymer battery according to claim 3, characterized in that: In step S2, the ratio of the amount of intermediate 1, AIBN, toluene and 3-mercaptopropanol used is 30.3 g:0.5 g:150 mL:9.2 g.
6. The process for preparing a polymer battery according to claim 3, characterized in that: In step S3, the ratio of the amount of polyacrylonitrile powder, zinc acetate dihydrate, ethanolamine and N,N-dimethylformyl is 20g:2g:25g:200mL.
7. The process for preparing a polymer battery according to claim 3, characterized in that: In step S4, the ratio of the amount of pre-modified polyacrylonitrile, N,N-dimethylformamide, and intermediate 2 is 20 g:200 mL:35 g.
8. The process for preparing a polymer battery according to claim 2, characterized in that: The raw materials are calculated in parts by weight as follows: 40-60 parts of modified polyacrylonitrile, 10-20 parts of tantalum-doped lithium lanthanum zirconium oxide, and 4-6 parts of lithium bis(trifluoromethanesulfonyl)imide.
9. The process for preparing a polymer battery according to claim 1, characterized in that: The mass ratio of lithium iron phosphate, polyvinylidene fluoride and acetylene carbon black is 6:2:1.
Citation Information
Patent Citations
Composite solid electrolyte, flexible all-solid-state battery, preparation method and wearable electronic device
CN106299467A
Polymer composite solid electrolyte preparation method and polymer composite solid electrolyte
CN112786951A
Preparation method and application of dual-modified solid electrolyte membrane
CN114335710A
Low-cost and high-film-forming-property organic / inorganic composite solid electrolyte membrane and preparation method thereof
CN118472372A
Fireproof flame-retardant fiber and preparation method thereof
CN118704109A